Inclusive Education Management for Children with Special Needs in Madrasah Ibtidaiyah - Syaefudin Achmad; Wan Alawee Samaeng (Universitas Islam Negeri (UIN) Salatiga, 2025)
Background & objectives: This article discusses the management of inclusive education in Madrasah Ibtidaiyah (MI), focusing on strategies and innovations, challenges and solutions, as well as the internalization of Islamic values in its implementation. Method: This qualitative case study at MI Tarbiyatul Aulad involved the principal and special needs teachers selected through purposive sampling, using planning, implementation, and reporting procedures with data collected via interviews, observation, and documentation. Data analysis involved data reduction, data presentation, and conclusion drawing. Results: The findings reveal: 1) five components of inclusive education management, namely initial assessment, curriculum adaptation, provision of special needs teachers, resource room and psychologist services; 2) two main challenges and their solutions in implementing inclusive education management; 3) three strategies for internalizing Islamic values, including the application of noble moral values, inclusive learning methods, and curriculum adjustments based on Islamic principles. Contribution of theory: The study reinforces the theory of Islamic education management grounded in the principles of tawafuq (harmony), ‘adl (justice), and rahmah (compassion). Limitations & Recommendations: A noted limitation is the lack of evaluation regarding the effectiveness and long-term impact of each component, suggesting the need for further research.